Corporate social responsibility in a burgeoning industry: a stakeholder analysis. Issue 1 (19th February 2018) - Alonso, Abel Duarte; Sakellarios, Nikolaos; Alexander, Nevil; O'Brien, Seamus
Abstract : Purpose: The purpose of this paper is to investigate the extent and significance of involvement of craft brewery operators in their community through the lens of the stakeholder theory (ST). In addition, differences between forms of involvement and demographic characteristics of operators and breweries are examined. Design/methodology/approach: As many as 218 operators of predominantly micro-craft breweries across the USA participated in an online questionnaire designed to gather their perceptions. Findings: While paying taxes was participants' main perceived form of contribution, providing an artisan-made product, the significance of the craft brewery as a community "hub", and that of increasing the number of leisure alternatives also emerged. A further 52.8 per cent of participants indicated contributing US$100, 000 or more to the community annually. Statistically significant differences were revealed, for instance, based on craft breweries' production volume, and the level of financial contribution. Various associations between operators' perceived contributions and the ST theses were established in regard to cooperative interests (descriptive), stakeholder management (instrumental), and moral principles (normative). Originality/value: First, by examining corporate social responsibility (CSR) in the craft brewing industry and among predominantly smaller firms, the study addresses two under-researched areas. Second, a refinement of the ST in the context of the craft brewing industry is proposed, highlighting the links between ST-based theses and the findings. Third, the study contributes to three different types of literature: micro and small business, craft brewing entrepreneurship, and CSR.